The Influence of Emotional Intelligence and Transformational Leadership on Organizational Commitment with Job Satisfaction asIntervening Variables in the State Gas Company Medan Branch Office - Nugraha Pratama; Kinanti Shandy Pramesti (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
The purpose of this study is to analyze several things, namely the influence of emotional intelligence, transformational leadership, and job satisfaction on organizational commitment, the influence of emotional intelligence and transformational leadership on job satisfaction, the influence of tional intelligence and transformational leadership on organizational commitment through job satisfaction. This study uses an associative research type with a sample of 52 respondents who are permanent employees at the State Gas Company, Medan Branch Office. Data collection techniques use a list of statements such as questionnaires and data analysis techniques use Path Analysis and to test the seven hypotheses proposed in this study using the Partial Least Square (SmartPLS) application. The results of the study show that the influence of emotional intelligence, transformational leadership, and job satisfaction on organizational commitment is positive and significant, the influence of emotional intelligence and transformational leadership on job satisfaction is positive and significant, the influence of emotional intelligence and transformational leadership on organizational commitment through job satisfaction is positive and significant.